Komputasi Statistik Tingkat Kunjungan Wisman dan Hunian Kamar Hotel di Indonesia: Sebelum dan Selama Pandemi Covid-19 - Fitriastuti, Lucia Ika; Vemberi, Yohannes; Herawan, Tutut (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The impact of the Covid-19 pandemic on tourist visits and hospitality has been enormous in various countries. This is due to social restriction policies and risks related to health. The purpose of this study is to prove quantitatively whether there are differences in the level of visits by foreign tourists and the occupancy rates of hotel rooms in Indonesia before and during the Covid-19 pandemic. This study uses 4 years of secondary data obtained from BPS from 2018 to 2022. The data analysis technique used is quantitative descriptive using a nonparametric statistical tool, namely the Wilcoxon Signes-Ranks Test. The results of this study indicate that there are differences in the level of foreign tourist visit and hotel rooms occupancy rates in Indonesia before and during the Covid-19 pandemic. It can also be proven that there were differences in the hotel rooms occupancy rates in Indonesia before and during the Covid-19 pandemic. Based on national data in Indonesia, the impact of the Covid-19 pandemic can reduce the level of foreign tourist visits and the occupancy rate of hotel rooms. This research recommends various innovative ways to deal with the negative impact of the Covid-19 pandemic on the tourism and hospitality industry.